Solvodynamics of TPGS 1000 in water: a sonochemical analysis / Fatin Amirah Abu Bakar - Abu Bakar, Fatin Amirah (2014)
Three different series of TPGS 1000 solution have been prepared (series A, B, C) having different concentrations using direct dissolution of the surfactant in the water. The present study deals with the solute - solvent interaction and its solvodynamic parameters during the direct dissolution of the TPGS 1000 in water. The experimental parameters such as density and ultrasonic velocity have been measured to further evaluate the solvodynamics parameters. The solvodynamic parameters such as isentropic compressibility (Ks), apparent isentropic molar compressibility (Ks<l>), internal pressure (ni), relative association (Ra), acoustic impedence (Z), vanderwalls free length (b) and free volume (V r) have been estimated so to understand the solute-solvent interactions within a system. It is observed that the density and the ultrasonic velocity values of the solution systems show an increase in trend with the increase in surfactant concentration. The observed trend can be ascribed to the fact of micellar dissociation. The estimated solvodynamic parameters, those complimented each other have been discussed in terms of the surfactant -solvent interactions which in tum support the contention of micellar dissociation.